2020
DOI: 10.1016/j.celrep.2020.108365
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Control of Distal Axon Integrity and Somal Responses to Axonal Damage by the Palmitoyl Acyltransferase ZDHHC17

Abstract: Highlights d The same enzyme, ZDHHC17, palmitoylates DLK and NMNAT2 d DLK palmitoylation by ZDHHC17 is essential for somal responses to axonal injury d Prolonged loss of ZDHHC17 causes NMNAT-dependent fragmentation of distal axons d Conserved motifs in NMNAT2 and DLK govern their ZDHHC17-dependent regulation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 74 publications
(152 reference statements)
1
60
1
Order By: Relevance
“…Finally, we asked whether this differential palmitoylation-dependent distribution might affect retrograde signaling by the DLK-JNK pathway, by assessing the somal response to Optic Nerve Crush (ONC), which requires both palmitoyl-DLK and JNK3 (Fernandes et al 2012; Fernandes et al 2014; Niu et al 2020; Watkins et al 2013; Welsbie et al 2013)(Fig 6D). ONC-induced c-Jun phosphorylation was markedly reduced in JNK3 KO mice and was ‘rescued’ by intravitreally injected HA-JNK3-WT AAV, but not by HA-JNK3-CCSS AAVs (Fig 6E, F).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, we asked whether this differential palmitoylation-dependent distribution might affect retrograde signaling by the DLK-JNK pathway, by assessing the somal response to Optic Nerve Crush (ONC), which requires both palmitoyl-DLK and JNK3 (Fernandes et al 2012; Fernandes et al 2014; Niu et al 2020; Watkins et al 2013; Welsbie et al 2013)(Fig 6D). ONC-induced c-Jun phosphorylation was markedly reduced in JNK3 KO mice and was ‘rescued’ by intravitreally injected HA-JNK3-WT AAV, but not by HA-JNK3-CCSS AAVs (Fig 6E, F).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that DLK palmitoylation is critical for initial responses to axonal injury and, unexpectedly, that this modification is also essential for DLK’s kinase activity in vitro (Holland et al 2016; Niu et al 2020). However, it was unclear from these studies whether palmitoylation controls other aspects of DLK pathway signaling, and why mammalian DLK couples to JNK, rather than to other MAPKs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations